The impact of balneotherapy on IL-6 cytokine levels, disease activity, functional ability, fatigue and depression in patients with rheumatoid arthritis - Aleksić-Milenković Ivana; Stojanović Sonja; Stamenković Bojana; Jevtović-Stoimenov Tatjana; Šarić Sandra; Danković Goran (Srpski Arhiv za Celokupno Lekarstvo)
Introduction/Objective. The aim of this study was to determine the impact of balneotherapy (BT) on IL-6 cytokine levels, disease activity, functional capacity, fatigue, and depression in patients with rheumatoid arthritis (RA). Methods. The study included 46 patients with RA (16 with moderate, 16 with low disease activity, and 14 in remission) who underwent BT as part of a rheumatic disease treatment program at the Niška Banja Institute for a duration of three weeks. BT was administered in the form of radon mineral baths (lasting 15–20 minutes in the thermo-mineral waters of Niška Banja at a temperature of up to 37°C). To evaluate the effect of BT, the study utilized ELISA kits for measuring plasma cytokine IL-6 levels, DAS28 SE and Clinical Disease Activity Index (CDAI) for assessing and calculating disease activity indices, the HAQ questionnaire for measuring functional ability, the Beck Depression Inventory (BDI), and the FACIT-F questionnaire for assessing fatigue. Results. Our research results showed that the application of BT led to a statistically significant improvement (p < 0.01, p < 0.001) in the values of all examined parameters: IL-6, DAS28 SE, CDAI, HAQ, FACIT-F, and BDI. Comparing the improvement in these parameters among groups of patients with different disease activity levels (moderate, low, remission), the most pronounced anti-inflammatory effect of BT was observed in patients with moderate disease activity. Conclusion. BT improved almost all observed parameters. Alongside medication therapy, BT is a significant part of the comprehensive therapeutic approach for RA patients.